Peran Bank Waqaf Mikro dalam Mengoptimalkan Waqaf Sebagai Instrumen Pemberdayaan Ekonomi - Sumarti, Retno Khabbatuni'mah; Susetyo, Achmad Budi (Jurnal Ekonomi dan Bisnis, 2025)
Waqf is an instrument of Islamic philanthropy that has great potential in sustainable economic development of the people. One form of innovation in the management of productive waqf in Indonesia is the establishment of the Micro Waqf Bank (BWM), which is present to provide access to sharia-based financing to low-income communities around Islamic boarding schools. This study aims to analyze the role of the Micro Waqf Bank in the management of productive waqf and formulate a strategy for optimizing waqf as an instrument for empowering the people's economy. The method used is library research with a qualitative approach. The results of the study show that BWM plays a significant role in increasing sharia financial inclusion, encouraging the growth of micro-businesses, and suppressing loan shark practices through collateral-free financing based on the Qardh contract. The strategy for optimizing waqf includes community education, strengthening the capacity of nazhir, innovation of waqf instruments, and synergy between stakeholders.   Wakaf merupakan instrumen filantropi Islam yang memiliki potensi besar dalam pembangunan ekonomi umat secara berkelanjutan. Salah satu bentuk inovasi dalam pengelolaan wakaf produktif di Indonesia adalah pembentukan Bank Wakaf Mikro (BWM), yang hadir untuk memberikan akses pembiayaan berbasis syariah kepada masyarakat berpendapatan rendah di sekitar pesantren. Penelitian ini bertujuan untuk menganalisis peran Bank Wakaf Mikro dalam pengelolaan wakaf produktif serta merumuskan strategi optimalisasi wakaf sebagai instrumen pemberdayaan ekonomi umat. Metode yang digunakan adalah studi pustaka (library research) dengan pendekatan kualitatif. Hasil kajian menunjukkan bahwa BWM berperan signifikan dalam meningkatkan inklusi keuangan syariah, mendorong pertumbuhan usaha mikro, dan menekan praktik rentenir melalui pembiayaan tanpa agunan berbasis akad Qardh. Strategi optimalisasi wakaf mencakup edukasi masyarakat, penguatan kapasitas nazhir, inovasi instrumen wakaf, dan sinergi antar pemangku kepentingan.